Modeling the factors affecting workplace well-being at construction sites : A cross-regional multigroup analysis - Afiqah R., Radzi; Anandh, K. S.; Ahmad Rizal, Alias; Algahtany, Mohammed; Abdul Rahimi, Abdul Rahman (Emerald Publishing, 2024)
A good workplace well-being (WWB) has many positive impacts on individuals and organizations. Prior studies indicate that physical, psychological and social well-being factors positively influence WWB. Nevertheless, it is essential to acknowledge that these factors may exhibit variations across different regions, cultural contexts and workplace environments. Therefore, this study aims to explore and validate the relationships between physical, psychological and social well-being factors and WWB at construction sites across different regions, using Malaysia and India as case studies. Design/methodology/approach: A conceptual model was proposed between physical, psychological and social well-being factors and WWB at construction sites. Then, a questionnaire survey was developed based on the proposed model and distributed to construction industry practitioners in both countries. In total, 316 responses were collected and analyzed using confirmatory factor analysis and multigroup analysis. Findings: The analyses indicate that the proposed model on physical, psychological and social well-being factors and WWB at construction sites is valid. Also, the model has no significant differences between the two countries. Thus, the findings show that the physical, psychological and social well-being factors are similarly affecting WWB at construction sites in both countries. Originality/value: The originality of the study lies in its holistic and cross-regional examination of WWB at construction sites. The insights gained from this study provide evidence for promoting good health and well-being in the construction industry. Moreover, this study seeks to provide insights that transcend geographical boundaries, offering valuable implications for promoting WWB practices in construction projects worldwide.